(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article delves into the differences, in politeness strategies between men and women. How these variations affect the way they communicate with each other. Politeness, in speech mirrors expectations and power dynamics shaped by gender norms. Women typically employ cooperative language that highlights forming connections whereas men usually opt for more direct communication centered around tasks. Nevertheless these tendencies are not. Can change depending on backgrounds, situational contexts and personal traits. Recognizing these distinctions could enhance how people connect with each other and increase recognition of prejudices, in communication.